Consistency of performance of early-maturing maize cultivars in Striga infested and Striga-free environments - Badu-Apraku, Baffour; Yallou, C.; Oyekunle, M.; Akinwale, R.; Aweke, G.; Kamara, A. (Agricultural Institute of Canada, 2015)
Badu-Apraku, B., Yallou, C., Oyekunle, M., Akinwale, R., Aweke, G. and Kamara, A. 2015. Consistency of performance of early-maturing maize cultivars in Striga-infested and Striga-free environments. Can. J. Plant Sci. 95: 1073–1084. Despite the immense potential of maize (Zea mays L.) in savannas of West and Central Africa (WCA), production and productivity is constrained by Striga hermonthica parasitism. Sixteen early-maturing cultivars were evaluated at two locations in Nigeria and three locations in the Republic of Benin from 2007 to 2009 to assess the grain yield, stability and the consistency of the rankings of the cultivars under Striga-infested and Striga-free environments. The combined analysis of variance showed significant (P<0.01) cultivar and cultivar×environment interactions for grain yield and other traits under Striga-infested and Striga-free environments. The test of concordance was significant (P<0.001) for grain yield (W=0.68), number of emerged Striga plants (W=0.74) and Striga damage (W=0.56) under Striga infestation, indicating stability of resistance in the cultivars developed from diverse sources under artificial S. hermonthica infestation across environments. There was high consistency of the rankings of the cultivars for grain yield and other Striga-resistance traits under Striga-infested and Striga-free environments in Benin and Nigeria. The additive main effects and multiplicative interaction (AMMI) biplot analysis for grain yield revealed POOL15SR/ACR94TZECOMP5-W/ACR94TZECOMP5-W and 2004 TZE-Y Pop DT STR C4 as the most stable cultivars with above-average mean grain yield in Striga-infested environments and they can be combined with other crop management options to control the parasite in the Striga endemic environments. Cultivars TZE Comp 5-W C7F2 and TZE Comp5-Y C6 S6 (Set B) had less Striga damage and number of emerged Striga plants across test environments. These cultivars could therefore serve as unique sources of favorable alleles for improving Striga resistance in maize in different production environments and farming systems.